Regional Collaborations as a Way Forward for Maternal, Newborn and Child Health: The South Asian Healthcare Professional Workshop (Journal of Health, Population and Nutrition, 2010)
This article reviews the importance of regional initiatives in the context of global efforts to achieve the Millennium Development Goal 4 and 5 and describes the action-oriented multi-country healthcare professional association (HCPA) workshops organized by the Partnership for Maternal, Newborn and Child Health. The South Asian HCPA workshop served as a catalyst for strengthening the ability of HCPAs in South Asian countries to organize and coordinate their activities effectively, play a larger role in national planning, and collaborate with other key stakeholders in maternal, newborn and child health. Key words: Capacity-building; Child health; Child welfare; Healthcare associations; Maternal health; Maternal welfare; Neonatal health; Regional collaboration; Workshops; Asia, South DOI: 10.3329/jhpn.v28i5.6149 J HEALTH POPUL NUTR 2010 Oct;28(5):417-423